Tingkat Kebisingan di Stasiun Poncol Semarang Berdasarkan Aspek Kenyamanan Audial - Simarmata, Karina; Setyowati, Erni (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2024)
The source of the noise level at the train station in several interior spaces including the VIP room, hall, office, market, and loco café by measuring in the field and carried out on September 15, 2023, at 12.33 WIB. The noise standard level based on the Decree of the Minister of Environment No. 48 of 1996 that the train station is 60 decibels. The purpose of this study is to determine the distribution of noise. The method used is a quantitative method by taking in the field and comparing the calibrated Sound Level Meter and Sound Meter Application within 3 minutes from the arrival of the train until the train departs. The results of the noise level of the five interiors of Semarang Poncol Station show that the noise level is greatest in the hall of Poncol station because the room is semi-open to make the sound that enters the room is very disturbed, and the noise level of the five rooms above the standard limit of the noise level. So it can be concluded that the room at Poncol Station experiences more noise than it should. The noise in the interior area of the station can exceed the specified comfort limit because of the different sound sources.